Suicide risk assessment and depressive symptoms among Spanish adolescent bully-victims: Evidence for the importance of emotional intelligence and sex. - Quintana-Orts, Cirenia Luz; Rey-Peña, Lourdes; Mérida-López, Sergio; Extremera-Pacheco, Natalio (Sage, 2023)
The aim of this study is to explore a model examining how emotional intelligence (EI), sex, depressive symptoms and suicidal thoughts and behaviours (STB) may interact. The sample included 380 Spanish adolescent bully-victims (61.6% boys; mean age = 14.38 years). The results indicated that EI is a significant negative predictor of decreased STB and that this relation is fully mediated by depressive symptoms. This effect was moderated by sex, such that the mediation is stronger for girls compared to boys. The promotion of EI may be core in the development of prevention programmes for suicide, especially among female bully-victims.
Keywords: Inteligencia emocional; Adolescentes - Salud mental; Ciberacoso; Internet y jóvenes; Diferencias sexuales (Psicología); Adolescence; bullying; Emotional intelligence; sex; suicide